All-in-one type ESIPT-active multi-stimuli responsive 7-diethylamino-4-hydroxycoumarin-rhodamine B hydrazone as molecular switches and the reversible photochromic features of its zinc ensemble. (20th October 2021) - Mathivanan, Moorthy; Tharmalingam, Balamurugan; Anitha, Ottoor; Lin, Chia-Her; Thiagarajan, Viruthachalam; Murugesapandian, Balasubramanian
Abstract : A new "all-in-one" type ESIPT-active multifunctional fluorescent compound (DHCRH ) exhibits methanol responsiveness, AIE, acidochromism and mechanochromic features. Interestingly its zinc ensemble shows reversible photochromic behaviour. Abstract : Multi-stimuli responsive fluorescent materials have vast applications in the field of chemistry, physics and material science. Among the multifunctional materials, ESIPT-active materials have drawn prodigious attraction in recent years due to their large Stokes shifted emission and dual emissive behavior. Herein, we report a novel "all-in-one" type fluorescent 7-diethylamino-4-hydroxycoumarin-rhodamine B conjugate (DHCRH ) which shows aggregation induced emission, acidochromism, and mechanochromic luminescent features along with unique methanol responsiveness. An information protection application was executed via a write-erase-write fluorescent platform using the acidochromic feature of DHCRH . Furthermore, the DHCRH-Zn ensemble was found to exhibit reversible photochromic behavior from a yellow to pink color in the solution state upon irradiation with 365 nm UV light through an intramolecular ring opening and closing mechanism. The complex provided a long lifetime for the ring-opened form and good fatigue resistance for reversible photochromism.